Early Outcomes and Complications of Synthetic Cartilage Implant for Treatment of Hallux Rigidus in the United States. Issue 4 (16th October 2019) - Cassinelli, Spenser J.; Chen, Stephanie; Charlton, Timothy P.; Thordarson, David B.
Category: Midfoot/Forefoot Introduction/Purpose: The aim of this study was to determine the outcomes and early complications following the implantation of a novel hydrogel synthetic cartilage implant (SCI) for the treatment of hallux rigidus by a single surgeon. This implant was FDA approved for implantation for the treatment of hallux rigidus in the United States in July 2016. Methods: A retrospective chart review of consecutive patients who underwent treatment for hallux rigidus with an SCI between August 2016 and June 2018 by a single surgeon was performed. Demographic information, radiographic assessment, and concomitant surgical procedures performed were evaluated for all patients. Post operatively, PROMIS physical function and pain scores, patient satisfaction, reoperation, conversion to arthrodesis, and need for further clinical treatment were collected. Seventy SCI were implanted in 65 patients. Follow up averaged 16.3 months (Range 6-27 months). Results: 16% (11/67) of patients were very satisfied, 31% (21/67) were satisfied, 22% (15/67) were neutral, 6% (4/67) were dissatisfied, and 24% (16/67) were very dissatisfied with their outcome. PROMIS physical function scores averaged 43, indicating mild dysfunction compared to population norms. PROMIS pain interference scores averaged 59, indicating mild pain compared to population norms. 50% (35/70) required a corticosteroid injection post-operatively. 24% (17/70) required advanced imaging with MRI post-operatively. There was a 13% reoperation rate for all-cause reoperation, and a 2.9% rate of conversion to arthrodesis. Subgroup analysis showed that patients undergoing Moberg osteotomy at time of SCI performed better than patients undergoing SCI alone. Conclusion: Synthetic cartilage implantation yielded modest patient satisfaction, mild dysfunction in physical measures, and a large proportion requiring further treatment and workup post operatively. We believe patient selection and counseling on the potential for continued pain and dysfunction in the early postoperative period following this procedure are important before proceeding with synthetic cartilage implantation for hallux rigidus.